(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
This paper presents data concerning the conditions of the population of two species of white pearl cornflowers – Centaurea appendicata Klokov and C. konkaе Klokov (section Pseudophalolepis Klokov) – on the banks of the Kakhovka Water Reservoir. Both species are extremely rare, local endemics of the lower Dnepr sands, included in the Red book of Ukraine. In the article the syntaxonomy of sandy communities with their participation are established, and the nature of the data population is presented. The factors influencing the decline of these species are determined in the article and measures to protect these species are proposed.